Cardiac arrest complicating cardiogenic shock: from pathophysiological insights to Impella-assisted cardiopulmonary resuscitation in a pheochromocytoma-induced Takotsubo cardiomyopathy—a case report. Issue 3 (22nd March 2021) - Zilio, Filippo; Muraglia, Simone; Bonmassari, Roberto
Abstract: Background: A 'catecholamine storm' in a case of pheochromocytoma can lead to a transient left ventricular dysfunction similar to Takotsubo cardiomyopathy. A cardiogenic shock can thus develop, with high left ventricular end-diastolic pressure and a reduction in coronary perfusion pressure. This scenario can ultimately lead to a cardiac arrest, in which unloading the left ventricle with a peripheral left ventricular assist device (Impella ® ) could help in achieving the return of spontaneous circulation (ROSC). Case summary: A patient affected by Takotsubo cardiomyopathy caused by a pheochromocytoma presented with cardiogenic shock that finally evolved into refractory cardiac arrest. Cardiopulmonary resuscitation was performed but ROSC was achieved only after Impella ® placement. Discussion: In the clinical scenario of Takotsubo cardiomyopathy due to pheochromocytoma, when cardiogenic shock develops treatment is difficult because exogenous catecholamines, required to maintain organ perfusion, could exacerbate hypertension and deteriorate the cardiomyopathy. Moreover, as the coronary perfusion pressure is critically reduced, refractory cardiac arrest could develop. Although veno-arterial extra-corporeal membrane oxygenation (va-ECMO) has been advocated as the treatment of choice for in-hospital refractory cardiac arrest, in the presence of left ventricular overload a device like Impella ®, which carries fewer complications as compared to ECMO, could be effective in obtaining the ROSC by unloading the left ventricle.